Self-perceived middle-distance race pace is faster in advanced footwear technology spikes - Montgomery Bertschy; Victor Rodrigo-Carranza; Ethan W.C. Wilkie; Laura A. Healey; Jeremy Noble; Wayne J. Albert; Wouter Hoogkamer (Journal of Sport and Health Science)
Background: Quantifying the potential benefits of advanced footwear technology (AFT) track shoes (i.e., “spikes”) in middle-distance events is challenging, because repeated maximal effort trials (as in sprinting) or aerobic running economy trials (as in long-distance running) are not feasible. Methods: We introduce a novel approach to assess the benefits of AFT spikes, consisting of a series of 200-m runs at self-perceived middle-distance race pace with 10 min recovery, and conduct 4 experiments to evaluate its validity, sensitivity, reproducibility, and utility. Results: In Experiment 1, participants ran 1.2% slower in spikes with 200 g added mass vs. control spikes, which is exactly equal to the known effects of shoe mass on running performance. In Experiment 2, participants ran significantly faster in AFT prototype spikes vs. traditional spikes. In Experiment 3, we compared 2 other AFT prototype spikes against traditional spikes on 3 separate days. Group-level results were consistent across days, but our data indicates that at least 2 separate sessions are needed to evaluate individual responses. In Experiment 4, participants ran significantly faster in 2 AFT spike models vs. traditional spikes (2.1% and 1.6%). Speed was similar between a third AFT spike model and the traditional spikes. These speed results were mirrored by changes in step length as participants took significantly longer steps in the 2 faster AFT spike models (2.3% and 1.9%), while step length was similar between the other spikes. Conclusion: Our novel, interval-based approach is a valid and reliable method for quantifying differences between spikes at middle-distance running intensity.